Development and Performance Test including Mechanical and Thermal of New Tenon Composite Block Masonry Walls - Hui Su; Dongyue Wu; Mengying Shen; Wei Chen; Shilin Wang (Advances in Materials Science and Engineering)
To improve the thermal performance of external masonry walls, a new tenon composite block is proposed as the external maintenance component which contains the internal hollow concrete block part, the external block part, and the extruded polystyrene layer fixed by tenons. The production process and concrete material mixing ratio were optimized for the new tenon composite block to promote its application. The mechanical strength and thermal properties of the optimized tenon composite blocks were tested with experiments and numerical simulation in this study. The testing and simulation results indicated that after utilizing the two optimized concrete mixing ratios, the tenon composite block strength matched the strength requirements according to the related design code. The thermal performance of the tenon composite block wall was also good compared with that of a common block wall.